A Study on Farmwomen Training Preference on Farm Implements - Shobhana Gupta and Shilpi Verma, (Indian Journal of Extension Education, 2016)
The study was aimed at determining women farmers' perception about importance, adequacy and need of training in farmimplements. A sample size of 240 women farmers was taken for the study and analyzed. Simple random samplingtechnique was used for the sample selection and structured questionnaire was used to elicit information from therespondents. Both descriptive and inferential statistics were used for data analysis. The result showed highest informationabout the repair of pump sets, oil engine; electric motor etc. was most important and most needed. Exposure to the use offarm implements was perceived as most adequate. It can be inferred that the rural women are in need of training inmajority of the areas in farm implements. Hence, there is a wide scope for the extension workers to organize and imparttraining to farm women in order to enhance their potential in adoption of improved technologies. Therefore, providingappropriate training in the area of farm implements to rural women will enable them in the updating their knowledge andenhancing in the skills.